The Role of Community Learning Activity Centers (PKBM) in the Context of Changing the Social Behavior of Street Children - Hikmat (International Journal of Science and Society, 2022)
This study aims to determine the role of the Community Learning Activity Center (PKBM) in changing the social behavior of street children. The learning model carried out in this study is about handling, the approach process action, and the form of socialization carried out by the Management and Experts at the Community Learning Activity Center for street children on the streets. It is hoped that with the guidance of street children in PKBM, it is expected that changes in the attitudes and social behavior of street children can be seen. The method used by the author in this study is qualitative. The data collection techniques used in this research are interview, observation, and literature study, including documentation. The results showed that the role of the Learning Activity Center in helping to change the social behavior of street children was perfect. However, here and there, there were still some shortcomings such as lack of discipline, self-confidence, and lack of care for the surrounding environment. The empowerment carried out by PKBM includes the development of life skills, academic activities, and religious activities.